Comparison of In Vivo Effects on Components of the Canine Fibrinolytic Enzyme System of AMCHA Fed at Varying Dose Levels - Celander, Evelyn; Celander, D. R (Thrombosis and Haemostasis, 1968)
Dogs were fed varying levels of trans-AMCHA (trans-4-aminomethyl-cyclohexane-1-carboxylic acid), a known inhibitor of the fibrinolytic enzyme system. Evidence that dialysis against citrate-veronal buffer in the cold for 24 hrs effectively removes AMCHA from plasma is presented. Determinations of antiactivator, antifibrinolysin, and proactivator were carried out on both dialyzed and undialyzed samples. At 55 mg/kg, a moderate immediate decrease in urokinase excretion occurred which was maintained throughout the time of drug administration. At higher levels, increases in antiactivator and decreases in proactivator and euglobulin lytic activity occurred, the extent of which could be roughly correlated with the amount of drug administered. No changes in either fibrinogen or antifibrinolysin were seen. An assay for the antiurokinase activity in canine plasma is described. The results are discussed in terms of the possible function of the fibrinolytic system as revealed by administration of inhibitors.